Analisis Finansial Usaha Agrowisata Kebun Kopi Rakyat Di Kecamatan Sungai Kakap Kabupaten Kubu Raya - Assiddiq, Hasbi; Dolorosa, Eva; Fitrianti, Wanti (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2024)
Agrotourism is a type of tourism that utilizes agricultural businesses as a tourist attraction. The aim is to broaden the recreational experience, knowledge, and support the improvement of agricultural products and to grow businesses in the agricultural sector. The development of agro-tourism in the coffee plantation area of Punggur Kecil Village was initiated as an effort to develop tourism that can support the preservation of the robusta coffee plant which has the potential to increase income and support welfare for the local community. The location of this research is in Punggur Kecil Village, Sungai Kakap District. The data used in this study are primary data and secondary data. Data analysis is using financial analysis with indicators: Net Present Value, Internal Rate of Return, Net Benefit Cost Ratio, Payback Period, Sensitivity Analysis. The results of this study indicate that: coffee plantation agrotourism is feasible by considering NPV = Rp. 303,591,645, IRR = 17%, Net B/C = 1.85, and payback period of 6.67 years. Sensitivity analysis with a 10% decrease in the number of visitors shows that this business is still feasible, while the sensitivity to changes in operational costs shows that this agro-tourism business is not feasible to run.